(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Obesity is a worldwide epidemic considered one of the main public health problems. For municipalities in the care of obesity in their territories, in the state of Espírito Santo, a course was held to face the development of workshops for the construction of the municipal plan to face obesity in the SUS, aimed at managers and professionals of Primary Health Care. Objective: The objective of this study was to identify advances, difficulties and potentialities in the implementation of the municipal plan to combat obesity prepared by managers and health professionals in ES, 2020. Methods: Descriptive, cross-sectional, quali-quantitative study developed with the 38 municipalities graduating from the course to fight obesity in Espírito Santo. Data were obtained between June and July 021 by completing the semi-structured course applied to. Descriptive statistics were performed for multiple choice questions and thematic content analysis for discursive questions. Results: The results indicate that 80% of the authors cited did not implement professional turnover due to COVID-19, which was the most important reason (7%),8 followed by high turnover (50.0%). Among those implementing the plan, care coordination is focused on medical professionals and nutritionists, and primary health care is the site of the initial approach in the follow-up flow. Conclusion: The construction of the plan in the cities presents many barriers that demand reorganization and municipal articulation to guarantee the integrality of the care.